Keragaman Gen Myxovirus (Mx) pada Itik di Kabupaten Indragiri Hulu Provinsi Riau - Restu Misrianti; Elfawati Elfawati; Apri Irianto (Musamus Journal of Livestock Science, 2022)
The Mx gene (Myxovirus) is a gene that functions to control the immunity of poultry against viral diseases. This gene is a native antiviral and is able to respond to influenza virus infections such as avian influenza. This study aims to identify the diversity of the Mx gene in ducks using the PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) molecular technique. The number of samples used were thirteen ducks from Indragiri Hulu Regency (Riau Province). The restriction site of the Mx gene using the Rsa1 enzyme is in the base sequence GTN|NAC. There are two alleles namely A and G, and three genotypes, AA, AG and GG. The results showed that the Mx gene in ducks was monomorphic. The frequency of the resistant allele (A) is 0%, while the frequency of the susceptible allele (G) is 100%.